Isolated Langerhans Cell Histiocytosis of Orbit: A Case Report and Review of the Literature. (4th April 2018) - Naik, Mayuresh; Mehta, Anuj; Mehrotra, Neha; Solanki, Anil
Abstract : A 2-year-old male child presented with a painless progressive mass in the inferolateral aspect of right orbit of three-month duration. Differential leucocyte count revealed raised eosinophil count (13%). On radiological examination, CT scan showed 25 × 27 mm round well-defined smooth-outlined homogenously enhancing extraconal mass arising from the zygomatic bone at the inferotemporal periorbital area of right orbit with bone erosion. Histopathological examination of the incision biopsy revealed characteristic Langerhans cells and immunohistochemical studies were positive for S-100 protein and adenosine deaminase. A diagnosis of Langerhans Cell Histiocytosis (LCH) was made and PET-CT revealed no other foci of uptake anywhere else in the body. The patient received 12 cycles of vinblastine, 0.2 mg/kg body weight, along with oral prednisolone, 1 mg/kg body weight. On completion of three cycles of chemotherapy, a reduction in size of the mass was noticed. A repeat PET scan was done 3 months after completion of chemotherapy did not reveal any activity noted previously.